Comparison of culture and polymerase chain reaction-restriction fragment length polymorphism for identification of various Capnocytophaga species from subgingival plaque samples of healthy and periodontally diseased individuals - Idate, Ulka; Bhat, Kishore; Kulkarni, R; Kotrashetti, Vijayalakshmi; Kugaji, Manohar; Kumbar, Vijay (Journal of oral and maxillofacial pathology : JOMFP, 2022)
Introduction: Capnocytophaga are facultative anaerobic Gram-negative bacilli and recognized as opportunistic pathogens of various extraoral infections. Only a few studies attempted to identify all the seven species of Capnocytophaga phenotypically and genotypically in healthy individuals and patients with chronic periodontitis. Studies to determine the prevalence of Capnocytophaga in subgingival plaque samples from healthy individuals, chronic gingivitis and periodontitis among Indian population are lacking. Aim: The aim of this study was to identify and compare the presence of Capnocytophaga species phenotypically through microbial culture and biochemical tests and genotypically through polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in subgingival plaque of healthy individuals and patients with chronic gingivitis and chronic periodontitis. Materials and Methods: A total of 300 subjects, 100 each with gingivitis, periodontitis and periodontally healthy gingiva subjected, were included. Subgingival plaque was collected and was cultured for phenotypic identification (microbial culture and biochemical test), and for genotypic identification, DNA extraction was done and PCR-RFLP analysis was performed to identify the genus Capnocytophaga and also to identify different species of Capnocytophaga. Results: Of 300 individuals, Capnocytophaga species were identified from 237 (79%) individuals by PCR and 82 (27.33%) by culture. The prevalence of Capnocytophaga ochracea was found to be higher with both the methods followed by Capnocytophaga gingivalis and Capnocytophaga granulosa. Capnocytophaga genospecies, Capnocytophaga leadbetteri and Capnocytophaga Sputigena were isolated only by culture with very low prevalence that is 1.33%, 1.33% and 0.66%, respectively. We could not get any isolate of Capnocytophaga haemolytica by any of the two methods. Conclusion: Capnocytophaga species could be found in gingival sulci as well as periodontal pockets and can be detected by culture and PCR-RFLP. However, higher prevalence of these species in healthy compared to disease requires further analysis to determine their role in healthy and diseased periodontium.